Strategi Internalisasi Nilai‑nilai Akhlak dalam Pendidikan Madrasah di Era Digital - Muhamad Januaripin; Ilman Nafi’a; Ubed Jubaedah; Munasir Munasir (Ideguru: Jurnal Karya Ilmiah Guru, 2025)
The advancement of digital technology in the era of the Fourth Industrial Revolution has significantly impacted various aspects of life, including how the younger generation shapes its identity and internalizes values. Generation Z, as digital natives, faces the risk of moral disintegration due to exposure to negative online content and the absence of strong value-based guidance. In this context, madrasahs—as educational institutions rooted in Islamic values—hold a strategic role. This article adopts an integrative conceptual approach to explore strategies for internalizing moral values in madrasah education, focusing on curriculum design, teacher role modeling, spiritual habituation, and the utilization of digital media. The discussion draws on recent scholarly literature and theoretical perspectives. The findings indicate that effective moral internalization requires a balanced integration of technology and spirituality. Furthermore, supportive educational policies, context-driven teacher training, and process-oriented character assessments are essential. Madrasahs should evolve into centers for value transformation, not merely institutions for knowledge transmission. Accordingly, the internalization of moral values remains normatively essential and adaptable within the dynamics of the digital age.